Application of factors in designing usability computerized adaptive testing (tai): a case study. - Maridueña Arroyave, Milton Rafael (Revista Universidad de Guayaquil, 2012)
The computer systems design should be guided by a set of concepts, principles and techniques, whose main objective is to minimize or reduce cognitive load and user perception, ie the result of the design process rise to a system (or tool) that demonstrates an easy and intuitive: indeed, assert the “usability” of the system. This goal, achieved through a process known as “user-centered”, it is necessary not only for improvements in user productivity and facilitate proper use of the systems developed, but it is a vital and practically mandatory for design of computerized adaptive tests that include people with functional dependence. A TAI generator software should be a friendly, easy to use, intuitive, portable, scalable, highly configurable and heavily documented, at the same time to respond to the specific objectives of an adaptive test based on Item Response Theory (IRT), similar systems fail the quality of its interfaces and how to interact with the user